Comparison of some biocomposite board properties fabricated from lignocellulosic biomass before and after Ionic liquid pretreatment - Mahmood, H. (Italian Association of Chemical Engineering - AIDIC, 2015)
The search for sustainable raw material is of critical importance with the ever-growing environmental concerns together with the diminishing fossil fuel resources. Lignocellulosic biomass is nowadays being considered as one of the most promising alternative feedstocks for the production of engineered composite materials. In this regard, various pretreatment technologies have been employed to increase the accessibility of polysaccharide portion of lignocellulose but development of an effective and environmental benign innovative pretreatment process remains challenging. Ionic liquids (ILs) have been emerged as novel solvent for green processing of lignocellulose for its effective utilization in biocomposite materials. In this work, effect of IL-assisted pretreatment of lignocellulosic biomass on the mechanical properties of thermo-moulded biocompoiste board was evaluated. Lignocellulosic residue oil palm frond (OPF) was pretreated with ILs: 1-butyl-3-methylimidazolium chloride BmimCl and 1-ethyl-3-methylimidazolium diethyl phosphate EmimDEP and fabricated into biocomposite board by using thermoplastic starch as biopolymer binder. Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) was performed to understand the effect of IL treatment on the OPF fibre. Mechanical properties (flexural strength and flexural modulus) of composite board made from untreated and treated fiber were measured. It was noted that IL pretreatment significantly improved the thermal stability of OPF fiber as well as the mechanical properties of the composite board. Thus, flexural strength of the biocomposite board fabricated from BmimCl and EmimDEP treated fiber was increased by 82 % and 70 % respectively as compared to untreated fiber composite board. ILs were successfully recycled and could be re-used. The present paper demonstrates that IL-assisted pretreatment could be a highly promising and green technology for effective utilization of lignocellulose in biocomposite field. Copyright Â© 2015, AIDIC Servizi S.r.l.,.